Analysis of the Key Concepts of Entrepreneurial Success and Its Applications - Rika Widya; Salma Rozana; Munisa Munisa; Rita Nofianti (Budapest International Research and Critics University, 2021)
Competition in the business world is getting tougher, making entrepreneurs have entrepreneurship that can achieve success in entrepreneurship—starting from starting a business that can continue to grow towards the competition that is being faced with continuing in a business environment that is very dynamic and full of uncertainty. This study aimed to determine the success factors of entrepreneurship according to Bob Sadino's concept. The informants in the research are the owners of the Berlian Pancing Shop Jl. Field Beetle Acid. To measure the failure or success of the informant in entrepreneurship, it can be linked to the entrepreneurship program that the informant has obtained. It can be said to be successful if the research took place at the time the entrepreneurship being undertaken experienced good development. However, it is said to have failed. If the study took place when the study took place, the informant experienced a decline in running his business. Based on the research that the author did, it turns out that the Berlian Pancing Shop Jl owner. Asam Kumbang Medan applies or applies the critical concepts of entrepreneurial success, according to Bob Sadino, where entrepreneurship can run and develop well if you use it. In this study, the researcher wants to combine the concept of successful entrepreneurship of Bob Sadino with the business of the owner of the Diamond Pancing Shop with the development of his business. The author describes the main discussion and sub-problems results in this thesis with descriptive qualitative methods and is reinforced by quantitative methods (mixed research). As for the data collection, researchers used field techniques, library techniques, observation, interviews, and accompanied by documentation.